Refining familiar constructs : alternative views in OB, HR, and I/O - Svyantek, Daniel J.; McChrystal, Elizabeth (Emerald Publishing Limited : IAP/Information Age Publishers, 2007)
This volume is based around 14 chapters and two critical analyses which provide new perspectives on important organizational constructs. The first half of the book provides chapters by advanced graduate students who are making their first contributions to understanding organizational behavior. The second half of the book provides chapters illustrating new views of organizational constructs but from the perspectives of more established researchers in the field. All chapters share a common theme of attempting to provide new ways of viewing organizations and organizational behavior. Each chapter is based on the premise that, when presented with problems that seem impossible to solve, often the best results are achieved by finding new perspectives on the basic constructs being studied. These new perspectives provide insights which illuminate the problems for the theory of organizations as well as improving the ability of organizational members to solve practical organizational problems.
Papers from IOOB 2005 (the Industrial Organizational Organizational Behavior Conference) held at the Florida Institute of Technology.
Keywords: Organizational behavior -- Congresses.; Industrial organization -- Congresses.; elektronické knihy; Conference papers and proceedings.; Business & Economics -- Organizational Behavior.; Organizational theory and behaviour.; electronic books